Equal Recognition: A Reply to Four Critics - Patten, Alan (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2015)
Equal Recognition seeks to restate the case in favour of liberal multiculturalism in a manner that is responsive to major objections that have been advanced by critics in recent years. The book engages, among other questions, with two central unresolved problems. First, how should ideas of culture and cultural preservation be understood, given widespread suspicion that these ideas rely on an unavowed, but objectionable, form of essentialism? And, second, what exactly is the normative basis of cultural rights claims, and what are the limits on those claims? My four commentators advance a variety of different criticisms of the book’s answers to these questions. I offer replies to each of their main challenges.